Transforming Indian Agriculture: Strategic Policies, Innovations, and the Role of KVK Centric Extension Systems for Sustainable Growth and Food Security: OPINION PAPER - K. D. Kokate (Annals of Arid Zone, 2025)
India is a major global agricultural player with a goal to produce over 354 million tonnes of food grains by 2025-26. Despite agriculture contributing about 18% to GDP and employing half the population, these figures are declining due to sector shifts. Since 1950, ICAR has revolutionized Indian agriculture through research, leading to significant increases in food, fisheries, and dairy production. The government has prioritized investment in research and extension, but current spending remains limited. Strengthening frontline institutions like KVKs and adopting digital tools are crucial for sustainable growth. To realize the vision of Vikasit Bharat @ 2047, it is vital to revisit the roles and mandates of extension institutions, implement policy reforms, enhance financial and human resources, and strengthen research-extension-farmer-market linkages. Promoting public-private-NGO partnerships will be essential for driving Innovation, Inclusivity, and Impact (3Is) within the agricultural system, ensuring resilient and inclusive growth for the future.